Proximal and distal spinal muscular atrophy in one family: molecular genetic studies provide further evidence for the non-allelic origin of both diseases. Issue 4 (April 1997) - Spranger, S; Rudnik-Schöneborn, S; Spranger, M; Schächtele, M; Zerres, K; Wirth, B
Abstract : We present the results of clinical and molecular genetic investigations of a family in which the father suffers from distal spinal muscular atrophy and the younger son is affected by infantile autosomal recessive SMA type I. The molecular analysis of the SMN gene showed homozygous deletions of telSMN exons 7 and 8 in the son only. This was probably the result of a new mutation in the paternal haplotype, since the affected boy did not inherit one copy of the marker Ag1-CA. These results indicate that distal and proximal SMA in this family are not caused by the same gene on chromosome 5q.